Analisis Kebutuhan Bahan Ajar Mata Kuliah Morfologi Tumbuhan - GH, Muliana; Anugra, Novia (Jurnal Biotek, 2023)
This research aims to determine the instructional needs of the Plant Morphology course. This qualitative descriptive study employed questionnaires and observation sheets to collect the data. The data were analyzed descriptively. The subjects of this study were 24 students majoring in biology in the Biology Science Program, enrolled in the third semester of 2022. According to the research findings, most students rely on online sources for their learning materials, with digital learning materials being the preferred choice for the Plant Morphology course. Students face difficulties in understanding the material and concepts in the Plant Morphology course, mainly because of the use of Latin in this course. The research shows that the teaching and learning activities are ineffective in terms of time because of the extensive material coverage. Several factors contribute to students' difficulties in learning plant morphology, such as the broad concepts, the learning media used, the students' intelligence, and a lack of interest and motivation. The overall teaching activities still rely on PowerPoint presentations. Students neglect reading the materials at home because there is no plant morphology course handbook. The study findings will serve as a reference for developing instructional materials in the Plant Morphology course that align with students' needs, motivating and supporting the achievement of learning objectives